Moscow sting : a novel - Dryden, Alex. (New York : Ecco, 2010)
Ex-KGB colonel Anna heads to America, where she is sought out by Adrian, the former boss of her deceased, ex-spy husband, who wants answers and information that only she possesses.
Originally published: London : Headline, 2009.
Keywords: Secret service -- Great Britain -- Fiction; Secret service -- Russia (Federation) -- Fiction; Spy stories